Penerapan Fuzzy Inference System Mamdani Untuk Menentukan Jumlah Pembelian Obat (Studi Kasus: Garuda Sentra Medika) - Rahmawati Rahmawati; Eka Pandu Cynthia; Intan Eria Elfi (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2019)
The availability of the right raw materials is closely related to the number of products to be produced. Therefore the prediction of production must be adjusted so that the stock order of raw materials can be calculated correctly. Inventory problems are problems that are always faced by decision makers in the field of inventory. Supplies are needed because basically the demand pattern is irregular. Inventories are carried out to ensure that there is certainty that when needed these products are available. The problem in inventory is the difficulty in determining the amount of inventory that must be provided in meeting the number of requests to consumers. The purpose of this study was to determine the amount of drug purchases at Garuda Sentra Medika with the Mamdani method fuzzy inference system based on inventory data and sales data. This study uses three variables, namely inventory, sales and purchases by having two inputs, namely inventory and sales and one output, namely purchase. The results of the application of the fuzzy inference system Mamdani method can help the company to determine the amount of drug purchases with a success rate of 99.35869%.Keywords: Drug Sales, Fuzzy Inference System, Inventory, Purchasing.